Move to improve - Prescribing physical activity and deprescribing paracetamol for low back pain: Protocol for a hybrid type III feasibility study - David Roberts; Paulo H Ferreira; Josielli Comachio; Paula R Beckenkamp; Thomas Patterson; Mark Halliday; Emma Kwan-Yee Ho (BMJ Open)
Introduction People experiencing low back pain (LBP) could potentially benefit from multimedia educational resources that integrate self-management strategies and improve awareness of the benefits of staying active and about medications that offer limited benefits, such as paracetamol. Primary care waiting rooms are potential spaces for presenting health promotion resources to improve health literacy through the dissemination of easily accessible health information. This feasibility study aims to explore the feasibility of conducting a large-scale trial to investigate the benefits of multimedia educational resources delivered at outpatient physiotherapy waiting rooms of public hospitals to support patients to participate in physical activity and reduce paracetamol intake for LBP.Methods and analysis A hybrid type III feasibility study will be conducted at a public hospital in Sydney, Australia, from March to September 2024. The multimedia strategy development (pre-implementation) involves collaborative planning among healthcare professionals, policymakers and community stakeholders in physiotherapy practice. Phase II (implementation) will evaluate the acceptability and implementation processes of delivering the multimedia educational resources in the physiotherapy waiting room following the RE-AIM (Reach, Effectiveness, Adoption, Implementation and Maintenance) framework. Findings from the quantitative data will be reported descriptively, and categorical data by counts and percentages. Qualitative (open-ended questions) will be integrated with the feasibility trial outcomes to inform the design of a full-scale randomised controlled trial.Ethics and dissemination This study has ethical approval from the Sydney Local Health District Human Research Ethics Committee (2023/ETH02683). The findings will be disseminated via peer-reviewed publications, articles in relevant newsletters and presentations at national and international conferences. Social media platforms including X will also be used to generate awareness.